Tourism and sustainable development in Algeria: Reality, challenges, and strategic planning prospects - Aissani, Abdelfatah; Nassour, Abdelkader; Hellal, Abdesselam (The International tax journal, 2025)
Tourism represents a fundamental driver of economic and social development through its role in job creation, attracting investments, and generating substantial financial revenues. In Algeria, the tourism sector demonstrates immense potential, positioning it as a pillar for national economic diversification. However, achieving its sustainability requires adopting an effective strategic planning approach. Therefore, this study aims to analyze the interaction between tourism and sustainable development in Algeria by assessing the current state of the sector and its alignment with sustainability requirements. The research paper employs an analytical methodology that integrates theoretical frameworks of sustainable tourism and development planning while evaluating their applications in the Algerian context. The findings reveal structural challenges hindering sectoral development, notably weak infrastructure, lack of investments, and insufficient supportive policies, juxtaposed with promising opportunities based on diverse natural and cultural resources. The study also highlights the importance of adopting an integrated planning model that balances economic dimensions (job creation, investment stimulation), environmental aspects (resource conservation), and social factors (cultural identity enhancement). The research recommends strengthening public-private partnerships, implementing flexible tourism policies, and emphasizing innovation in tourism marketing to ensure the transformation of challenges into sustainable development opportunities.